Tradisi Rajaban Menurut Agama Buddha - Eko Siswoyo; Suyatno, Tri; Saras (PATISAMBHIDA : Jurnal Pemikiran Buddha dan Filsafat Agama, 2025)
The Rajaban tradition is a cultural practice of the Javanese people which is carried out in the month of Rajab as a form of respect and prayer for ancestors, which functions as well as a religio-cultural rite and a medium of social cohesion. This study aims to analyze the Rajaban tradition from the perspective of Buddhist teachings, especially through the concept of pattidana (bestowal of services). The research uses a qualitative approach of a case study in Widarapayung Kulon Village, Binangun District, Cilacap Regency, with observation, interview, and documentation techniques. The analysis was carried out in a descriptive-interpretive manner. The results of the study show the alignment of values between the practice of Rajaban and the teachings of Dhamma Buddha in the aspects of devotion to ancestors, the development of virtues, and the strengthening of social solidarity, so that the local tradition can be understood as an expression of pattidana if interpreted according to the principles of the Dhamma.